1969
DOI: 10.1111/j.1365-2133.1969.tb16002.x
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Dermatitis.

Abstract: SUMMARY.— One hundred and six rubber sensitive patients are described. Seventy had developed dermatitis from specific rubber articles such as household gloves, condoms, footwear and girdles. In the remaining 36 cases dermatitis was due to contact with rubber in various different forms. A formidable number of chemical additives are used by the rubber industry and many of these are potential skin sensitizers. In the present series, however, sensitivity was attributed to a thiuram accelerator or mercaptobenz‐thia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 6 publications
(3 reference statements)
2
10
0
Order By: Relevance
“…This agrees with reports from other countries, (9)(10)(11). Rubber gloves are a frequent cause of rubber eczema (3,4) and the present study showed that gloves were responsible for the majority of our cases. The positive patch tests were considered relevant and the patients granted financial compensation from insurance companies.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This agrees with reports from other countries, (9)(10)(11). Rubber gloves are a frequent cause of rubber eczema (3,4) and the present study showed that gloves were responsible for the majority of our cases. The positive patch tests were considered relevant and the patients granted financial compensation from insurance companies.…”
Section: Discussionsupporting
confidence: 55%
“…Glove materials, especially rubber, but also plastics can cause allergic eczema (1)(2)(3)(4). We analysed the incidence of rubber and plastic glove dermatitis at our institute over a 10-year period and tried to identify the specific allergens.…”
mentioning
confidence: 99%
“…[1976], rubber additives are among the most frequent causes of contact dermatitis. Hand eczema attributable to rubber glove sensitivity has been described by Bonnevie and Marcussen [1945], Sidi and Hincky [1965], Wilson [1969] and others. The use of rubber gloves as a precautionary measure to protect workers against various allergens has, on the contrary, been responsible in itself for a rather high incidence of derma titis; therefore, the worker, in avoiding one allergy, subjects himself to another.…”
Section: Discussionmentioning
confidence: 99%
“…The numerous positive reactions caused by carba mix may be of allergic or irritant origin, a problem which has been brought up by Wilson [1969] and Rudzki el at. [1976] and is now being investigated by ourselves.…”
Section: Discussionmentioning
confidence: 99%
“…However, during the manufacturing process of natural or synthetic rubber additives are used which may sensitize both manufacturer and consumer. Among these additives, some accelerators like thiurams or mercaptobenzothiazole compounds are known as strong sensitizers [1], Regarding consumers, pre vention of rubber dermatitis in housewives is possible by advising to wear PVC gloves. Surgeons or nurses with hand dermatitis caused by rubber gloves are often allergic to thiurams [2], These patients are sometimes advised to wear 'hypo-allergenic' gloves [3] which often means that thiurams have been replaced by dithiocarbamates.…”
Section: Introductionmentioning
confidence: 99%